Die Verteilung der potentiellen Verdunstung in Ägypten - Haude, Waldemar (ERDKUNDE, 1959)
The most purposive use of the rather limited waters of the Nile is of foremost importance for the development of agriculture in Egypt. For this reason, it is necessary to obtain more exact quantitative figures on the evaporation of irrigated land as well as on evapotranspiration of different crops. Hence investigations were carried out at the recently established Agrometeorological Station near Cairo, in 1957. Potential evaporation and evapotranspiration were measured, and their relation to the actual figures of different soils, with and without vegetation, ascertained. The results are used in connection with suitable climatological data to ascertain the potential evaporation also for other places, and to compute the actual figures. These are the basis of a theoretical computation of the water supply in the Mediterranean costal regions. In addition, potential evaporation - as computed above -is shown in its dependence upon latitude and distance from the sea. Thus, regional data of evapotranspiration are ascertained, and then compared with the quantity of water that is taken away from the Nile for irragation.